Exploring The BTS ARMY Fandom: A Comprehensive Review - Wira Saputri, Kadek Pradnyasari; Lammertz, Sina (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
This comprehensive review explores the BTS ARMY fandom within the context of globalization and technological advancements. As societies increasingly interact across cultural boundaries, the emergence of South Korean culture, particularly represented by BTS, has become a significant phenomenon. Through a qualitative desk research approach, utilizing secondary data analysis of existing literature, this study delves into the nature of fandoms, specifically focusing on the ARMY community. The objectives encompass understanding the importance of the topic, reviewing the state of the art and previous research, and elucidating the dynamics of ARMY fandom within the context of globalization. By examining existing studies and theories, this research seeks to provide insights into the characteristics and behaviors of ARMY fandom members. The findings contribute to a deeper understanding of how technology and globalization shape contemporary fan cultures, with implications for broader social and cultural processes. This review underscores the significance of ARMY fandom as a global cultural phenomenon and highlights avenues for future research in fan studies. Keywords: BTS, ARMY fandom, globalization, fan studies, social and cultural processes